Commercial investors and access to land - Gavian, S.; Degefa, G. (Ethiopian Development Research Institute, 1994)
The first part of the paper describes the investment code in general and the agricultural code in particular. It lists the criteria to the issuance of operating license to domestic investors, and discusses about other licenses. The paper looks into the response by investors in commercial agriculture with particular reference to field data on agricultural investment projects, types of activities, inputs, land and community contributions. Issues faced by investors in commercial agriculture is also discussed. This includes high cost of doing business, financial challenges, poor infrastructure, corruption, issues raised by commercial agriculture, and competition for land resources.